2001
DOI: 10.1007/s005340170049
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte transplantation: new horizons and challenges

Abstract: Hepatocyte transplantation represents an alternative strategy for treating liver disease. Liver repopulation following acute liver failure could, potentially, eliminate the requirement for orthotopic liver transplantation. Similarly, the ability to repopulate the liver with disease-resistant hepatocytes offers new opportunities for correcting genetic disorders and treating patients with chronic liver disease. Recent advances concerning the fate of transplanted cells in the recipient liver, the efficacy of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 77 publications
(191 reference statements)
2
32
0
Order By: Relevance
“…31 Our finding of donor cell engraftment frequencies at 4 weeks post-transplantation was in line with those previously reported. Although differentiation of some of the transplanted donor cells into hepatocytes was detected, consistent with those reported by Sato et al 26 and Aurich et al, 27 the combined findings of predominant repopulation by murine cells, the superior rescuing potential of MSCs over MDHs, as well as the ability to rescue FHF in such a short period suggest that differentiation of donor cells into hepatocytes was not the primary attribute.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…31 Our finding of donor cell engraftment frequencies at 4 weeks post-transplantation was in line with those previously reported. Although differentiation of some of the transplanted donor cells into hepatocytes was detected, consistent with those reported by Sato et al 26 and Aurich et al, 27 the combined findings of predominant repopulation by murine cells, the superior rescuing potential of MSCs over MDHs, as well as the ability to rescue FHF in such a short period suggest that differentiation of donor cells into hepatocytes was not the primary attribute.…”
Section: Discussionsupporting
confidence: 82%
“…31 By 3 months posttransplantation, human B2M-positive cells were below the sensitivity of detection, and thus we adapted a real-time genomic DNA polymerase chain reaction-based approach previously reported in the literature. 32 Although human cells were detectable by this approach, frequencies were estimated to be 0.001%-0.01% in the liver at both 3 and 6 months posttransplantation, conceivably due to the dilution of donor-derived cells as a result of normal tissue turnover.…”
Section: Transplanted Donor Cells Engraft In the Liver And Can Differmentioning
confidence: 99%
“…27,28 Furthermore, the potential ability to replace the liver with genetically modified disease-resistant hepatocytes may offer new insights into correcting genetic disorders and treating patients with chronic liver diseases. 29,30 Although the use of human ES cells for therapeutic purposes must 31,32 to date, convincing results have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44] A first animal study showed a possible application of isolated fetal hepatocytes for the correction of a metabolic disorder; the intrasplenic transplantation of normal fetal hepatocytes in analbuminemic rats led to a repopulation of the diseased liver with healthy donor hepatocytes and a normalization of albumin levels. 45 The role of fetal liver stem cells for new therapeutic applications has yet to be defined; in addition to the theoretical risks from the use of undifferentiated cells, the legal and ethical issues have to be addressed in the scientific community.…”
Section: ™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™™mentioning
confidence: 99%